Optimization of Near-Infrared Fluorescence Voltage-Sensitive Dye Imaging for Neuronal Activity Monitoring in the Rodent Brain - Pak, Rebecca W.; Kang, Jeeun; Boctor, Emad; Kang, Jin U. (Frontiers in Neuroscience, 2021)
Many currently employed clinical brain functional imaging technologies rely on indirect measures of activity such as hemodynamics resulting in low temporal and spatial resolutions. To improve upon this, optical systems were developed in conjunction with methods to deliver near-IR voltage-sensitive dye (VSD) to provide activity-dependent optical contrast to establish a clinical tool to facilitate direct monitoring of neuron depolarization through the intact skull. Following the previously developed VSD delivery protocol through the blood-brain barrier, IR-780 perchlorate VSD concentrations in the brain were varied and stimulus-evoked responses were observed. In this paper, a range of optimal VSD tissue concentrations was established that maximized fluorescence fractional change for detection of membrane potential responses to external stimuli through a series of phantom, in vitro, ex vivo, and in vivo experiments in mouse models.